2019
DOI: 10.1002/chem.201904156
|View full text |Cite
|
Sign up to set email alerts
|

Formal Lossen Rearrangement/Alkenylation or Annulation Cascade of Heterole Carboxamides with Alkynes Catalyzed by CpRhIII Complexes with Pendant Amides

Abstract: It has been established that a cyclopentadienyl (Cp) RhIII complex with two aryl groups and a pendant amide moiety catalyzes the formal Lossen rearrangement/alkenylation cascade of N‐pivaloyl heterole carboxamides with internal alkynes, leading to alkenylheteroles. Interestingly, the use of sterically demanding internal alkynes afforded not the alkenylation but the [3+2] annulation products ([5,5]‐fused heteroles). In these reactions, the pendant amide moiety of the CpRhIII complex may accelerate the formal Lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 137 publications
1
5
0
Order By: Relevance
“…Based on the above results and previous reports, [10–11,12–19] a plausible mechanistic scenario is outlined (Scheme 7). The reaction is initiated by a concerted metalation deprotonation (CMD) of 1 a at the C6 position to generate the rhodacyclic intermediate A4 .…”
Section: Resultssupporting
confidence: 56%
See 1 more Smart Citation
“…Based on the above results and previous reports, [10–11,12–19] a plausible mechanistic scenario is outlined (Scheme 7). The reaction is initiated by a concerted metalation deprotonation (CMD) of 1 a at the C6 position to generate the rhodacyclic intermediate A4 .…”
Section: Resultssupporting
confidence: 56%
“…In particular, a variety of fused polycyclic (hetero)arenes have been prepared by chelation‐assisted ortho C−H activation followed by a second C−H functionalization (sometimes called rollover C−H activation) [7n,15] . Importantly, contributions from the groups of Xu, [11g] Rodriguez, [11i] Choudhury, [11k,q] Feng, [11n,16] Tanaka [17] and Zhu [18] revealed that the reaction pathways can be diverted between C−H alkenylation and annulation of heteroarenes with internal alkynes, allowing access to distinct products from the same reactants. This switching of reaction pathways can be efficiently controlled by modification of reaction conditions or variation of the substrate structure.…”
Section: Introductionmentioning
confidence: 99%
“…One of the authors of this study (K.T.) has developed amide‐pendant cyclopentadienyl rhodium (Cp A Rh III ) catalysts [11b,d, 14] and a bis(ethoxycarbonyl)‐substituted cyclopentadienyl rhodium (Cp E Rh III ) catalyst (Scheme 1b, c). [11a,c, 15] These rhodium catalysts also exhibit high and/or unique reactivity for several C−H functionalization reactions [14, 15]…”
Section: Introductionmentioning
confidence: 99%
“…In particular, following the pioneering works on C2‐alkenylation of indoles with internal alkynes by Fagnou [2a] and oxidative annulation of 1‐phenyl‐1 H ‐pyrazoles with internal alkynes by Miura and Satoh, [2b] Cp*Rh(III) complexes have been extensively applied in direct alkenylation and oxidative annulation of (hetero)arenes with internal alkynes [3–5] . Moreover, independent studies by Xu, [3g] Carretero, [3i] Choudhury, [3j] Tanaka, [5f] Zhu [5g] and us [5i] have disclosed that varying the reaction conditions or the substrate structures can enable the reaction pathways to switch between alkenylation and annulation, allowing divergent synthesis of different products from the same starting materials. Despite these impressive achievements with internal alkynes, there has been limited success in Rh(III)‐catalyzed direct functionalization of C−H bonds with terminal alkynes probably due to their strong tendency to oligomerize and undergo other side reactions.…”
Section: Introductionmentioning
confidence: 99%